Pharmacogenetic associations of MMP9 and MMP12 variants with cardiovascular disease in patients with hypertension. - Rikki M Tanner; Amy I Lynch; Victoria H Brophy; John H Eckfeldt; Barry R Davis; Charles E Ford; Eric Boerwinkle; Donna K Arnett (PLoS ONE)
Objectives MMP-9 and -12 function in tissue remodeling and may play roles in cardiovascular disease (CVD). We assessed associations of four MMP polymorphisms and three antihypertensive drugs with cardiovascular outcomes. Methods Hypertensives (n = 42,418) from a double-blind, randomized, clinical trial were randomized to chlorthalidone, amlodipine, lisinopril, or doxazosin treatment (mean follow up, 4.9 years). The primary outcome was coronary heart disease (CHD). Secondary outcomes included combined CHD, all CVD outcomes combined, stroke, heart failure (HF), and mortality. Genotype-treatment interactions were tested. Results There were 38,698 participants genotyped for at least one of the polymorphisms included here. For MMP9 R668Q (rs2274756), lower hazard ratios (HRs) were found for AA subjects for most outcomes when treated with chlorthalidone versus amlodipine (eg., CCHD: GG = 1.00, GA = 1.01, AA = 0.64; P = 0.038). For MMP9 R279Q (rs17576), modest pharmacogenetic findings were observed for combined CHD and the composite CVD outcome. For MMP12 N122S (rs652438), lower HRs were observed for CHD in subjects carrying at least one G allele and being treated with chlorthalidone versus lisinopril (CHD: AA = 1.07, AG = 0.80, GG = 0.49; P = 0.005). In the lisinopril-amlodipine comparison, higher HRs were observed for participants having at least one G allele at the MMP12 N122S locus (CHD: AA = 0.94, AG = 1.19, GG = 1.93; P = 0.041). For MMP12 -82A>G (rs2276109), no pharmacogenetic effect was found for the primary outcome, although lower HRs were observed for AA homozygotes in the chlorthalidone-amlodipine comparison for HF (P = 0.015). Conclusions We observed interactions between antihypertensive drugs and MMP9 and MMP12 for CHD and composite CVD. The data suggest that these genes may provide useful clinical information with respect to treatment decisions.